Perceiving a Resourcefulness: Longitudinal Study of the Sequential Mediation Model Linking Between Spiritual Leadership, Psychological Capital, Job Resources, and Work-to-Family Facilitation - Jiao, Pei; Lee, Changshien (Frontiers in Psychology, 2021)
In order to improve our understanding of whether and how spiritual leadership promotes positive work-family outcomes from a resource perspective, this study proposed and tested for the first time the conceptual model incorporating job resources to psychological capital link as the mediating process between spiritual leadership and facilitation. Using Hayes’ (2018) multiple mediation analysis framework (Model 6), this study analyzed the data from 529 Chinese workers who completed questionnaires in a four-wave survey. The results showed that perceived spiritual leadership had a significant positive effect on employee work-to-family facilitation. The relationship between spiritual leadership and work-to-family facilitation was mediated by job resources alone, as well as job resources and psychological capital in sequence. Thus, this research may also pave the way for future spiritual leadership research on follower outcomes in other domains (e.g., community and school) by shifting the present spiritual leadership research focus from work outcomes to personal life. Implications for theory, managerial practices, limitation, and future research were discussed.